3(3x-9)-14x=-(6x+5)

Simple and best practice solution for 3(3x-9)-14x=-(6x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-9)-14x=-(6x+5) equation:


Simplifying
3(3x + -9) + -14x = -1(6x + 5)

Reorder the terms:
3(-9 + 3x) + -14x = -1(6x + 5)
(-9 * 3 + 3x * 3) + -14x = -1(6x + 5)
(-27 + 9x) + -14x = -1(6x + 5)

Combine like terms: 9x + -14x = -5x
-27 + -5x = -1(6x + 5)

Reorder the terms:
-27 + -5x = -1(5 + 6x)
-27 + -5x = (5 * -1 + 6x * -1)
-27 + -5x = (-5 + -6x)

Solving
-27 + -5x = -5 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-27 + -5x + 6x = -5 + -6x + 6x

Combine like terms: -5x + 6x = 1x
-27 + 1x = -5 + -6x + 6x

Combine like terms: -6x + 6x = 0
-27 + 1x = -5 + 0
-27 + 1x = -5

Add '27' to each side of the equation.
-27 + 27 + 1x = -5 + 27

Combine like terms: -27 + 27 = 0
0 + 1x = -5 + 27
1x = -5 + 27

Combine like terms: -5 + 27 = 22
1x = 22

Divide each side by '1'.
x = 22

Simplifying
x = 22

See similar equations:

| 5s-7=6s | | -2(0)+y=3 | | -7x=-91 | | y+-1(0.6666666666666667)*3=-2 | | 3+2y=3y | | (s+5)(s-12)=0 | | y-(0.6666666666666667)0=-2 | | 2z^2=7z | | -3x+7=-2x | | 2(-7)+7y=0 | | 20x^2+245= | | 11y-16-15=2(45) | | -7+5s=6s | | 7(2-2n)+5=-2(5n-5) | | -5p-7=-5+43 | | -3y=-24 | | 5(-4)+4y=0 | | 2.5x+0.5x=5x+22+3.5x | | -4(1)+y=5 | | 2z=-82 | | -4(0)+y=5 | | 0.15+0.5x=0.4 | | 6x^2-13x=28 | | 6z^2-7z-20=0 | | -8+11s=12s | | .05x+.20(100)=.1(100+x) | | -2+y=6 | | 0.5x-1=1.5 | | 4r+7r=88 | | 6-3x=5x-10x+10 | | 75x^2-91x-12= | | x^1-5x=0 |

Equations solver categories